2018
DOI: 10.1016/j.ijfatigue.2018.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Predicting fretting fatigue in engineering design

Abstract: The progress in fretting fatigue understanding and predictability is reviewed, with engineering applications in mind. While industrial assessments often relies on simple empirical parameters, research in fretting fatigue should allow the the design engineer to improve confidence in the fretting fatigue analysis.Fretting fatigue cracks often form in multiaxial stress fields with severe gradients under the contact area, and are inherently difficult to predict.By describing the fretting stress gradients using com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 160 publications
(246 reference statements)
0
16
0
Order By: Relevance
“…These structures are subjected to external loads while suffering fretting damage, such as tension and compression, bending, torsion, and combined loads 2–5 . Under the combined action of fretting fatigue and fretting wear, fretting cracks will appear on the surface, which greatly reduces the fatigue limit of the structure 6–9 . Studies have shown that fretting can reduce the fatigue strength of the material by up to 50% and the life span by more than 30% 10 …”
Section: Introductionmentioning
confidence: 99%
“…These structures are subjected to external loads while suffering fretting damage, such as tension and compression, bending, torsion, and combined loads 2–5 . Under the combined action of fretting fatigue and fretting wear, fretting cracks will appear on the surface, which greatly reduces the fatigue limit of the structure 6–9 . Studies have shown that fretting can reduce the fatigue strength of the material by up to 50% and the life span by more than 30% 10 …”
Section: Introductionmentioning
confidence: 99%
“…7 For decades, the fretting fatigue mechanism has been well studied. 8,9 A uniform fretting fatigue model (as shown in Figure 1(a)) was gradually formed. It was wildly used in experimental and numerical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…22 Cyclic loading causes these microwelds to break, forming wear debris. 23,24 The microcracks near the edge of the contact zone dominate the crack initiation life.…”
Section: Introductionmentioning
confidence: 99%